Reframing State Loss Policy in Price-Related Corruption Cases: A Future Agenda - Firmansyah, Amir; Mohammad Abdallah Alshawabke; Suzali Sulaiman; Jan Alizea Sybelle (Contrarius, 2026)
State losses from corruption cases in Indonesia are commonly interpreted solely as financial losses, while broader economic losses are largely overlooked. Corruption generates impacts that extend beyond fiscal depletion, affecting economic stability, social welfare, ecological integrity, and other systemic dimensions. This study therefore aims, first, to identify and examine the challenges arising from the ambiguous definition of state loss in Indonesia’s legal framework, particularly in price-related corruption cases; second, to analyse Singapore’s conduct-based model of corruption enforcement, which does not treat state loss as an element of the offence; and third, to formulate an ideal normative framework that can strengthen Indonesia’s anti-corruption regime. Using a normative legal research method with statutory, comparative, and conceptual approaches, this study finds that the ambiguity of the state-loss concept has made it difficult to establish economic losses in court, leading judges to focus exclusively on financial loss and leaving broader economic harm unaddressed in judicial decisions. In contrast, Singapore’s approach, by excluding state loss as an element of corruption, allows enforcement to centre on gratification and corrupt intent, resulting in a more coherent and efficient process than the Indonesian model. Consequently, a reframing of the state-loss concept is required, including more precise parameters of economic loss within anti-corruption law, standardised methodologies for its calculation, and broader asset-recovery mechanisms to enhance legal certainty and improve the overall effectiveness of corruption enforcement.